2022
DOI: 10.3390/life12091410
|View full text |Cite
|
Sign up to set email alerts
|

Role of WRKY Transcription Factors in Regulation of Abiotic Stress Responses in Cotton

Abstract: Environmental factors are the major constraints in sustainable agriculture. WRKY proteins are a large family of transcription factors (TFs) that regulate various developmental processes and stress responses in plants, including cotton. On the basis of Gossypium raimondii genome sequencing, WRKY TFs have been identified in cotton and characterized for their functions in abiotic stress responses. WRKY members of cotton play a significant role in the regulation of abiotic stresses, i.e., drought, salt, and extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…WRKY and bHLH transcription factors play an important role in plants’ heavy metal stress defense ( Guo et al., 2022 ). However, little information is available about the Cd-responsive WRKYs and bHLHs in tomato ( S. lycopersicum ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…WRKY and bHLH transcription factors play an important role in plants’ heavy metal stress defense ( Guo et al., 2022 ). However, little information is available about the Cd-responsive WRKYs and bHLHs in tomato ( S. lycopersicum ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the current study has emphasized identifying and characterizing two large and very important families of TFs, i.e., WRKY and bHLH gene families, in tomato plants. The detailed composition and mode of action of both WRKY and bHLH TFs are well-explored ( Heim et al., 2003 ; Chen et al., 2019 ; Hao et al., 2021 ; Wani et al., 2021 ; Guo et al., 2022 ). Here, we will focus on the comparative genomic studies and functional roles of WRKY and bHLH TFs in tomato, particularly in heavy metal defense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that genes related to TFs play critical roles in response to salt stress in other plants. For example, the WRKY TFs of cotton play a significant role in the regulation of abiotic stresses (i.e., salt, drought, and extreme temperatures) [ 91 ]; MYB TFs are involved in the responses to different abiotic stresses, such as salt, cold, and drought, and the FvMYB82 gene probably plays an important role in the response to salt and cold stresses in Arabidopsis thaliana by regulating downstream related genes [ 92 ]; and NAC TFs play vital roles in plant development and responses to various abiotic stresses, and the ThNAC4 gene of Tamarix hispida is involved in salt and osmotic stress tolerance [ 93 ]. In this study, 16 TFs were directly associated with stress response and seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…A typical WRKY motif has therefore been suggested, embracing the consensus sequence W(R/K)(K/R)Y [ 5 ]. According to the number of WRKY domains and the type of zinc-finger motif, WRKY proteins can be divided into three major groups, Group I, Group II, or Group III [ 6 ]. Those in Group I contain two WRKY domains and one C 2 H 2 (C-X 4-5 -C-X 22-23 -H-X 1 -H) zinc finger motif; Group II includes proteins with one WRKY domain and a C 2 H 2 zinc finger motif, and can be further divided in five subgroups (IIa, IIb, IIc, IId and IIe) according to the primary amino acid sequence [ 7 ].…”
Section: Introductionmentioning
confidence: 99%